An Unfortunate Refutation: Ibn Taymīyah on the Priority of Reason over Revelation - Ahmad, Choirul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
Ibn Taymīyah singled out his long refutation against an Ash‘arite theologian Fakhr al-Dīn al-Rāzī on ta’wīl in his Dar’ Ta‘āruḍ al-‘Aql wa al-Naql. The main contention between the two is whether rational evidence should take precedence over scriptural evidence when interpreting passages in the Qur’an. When dealing with the difficult passages that could lead to anthropomorphism, the Ash‘arite employ allegorical interpretation, or ta’wīl, thereby priority is given to reason. It is with this problem in mind that Ibn Taymīyah launched his sustained critique towards al-Rāzī. However, upon further consideration, Ibn Taymīyah’s criticism of al-Rāzī appears to overlook the broader framework that the latter brought to the discussion, particularly regarding the reciprocal relationship between reason and revelation in his theory of inference and its origins in earlier Asharīte’s epistemology. This article aims to discuss the debates between the two scholars by putting their main contention in the context. Firstly, the article will provide an analysis on al-Rāzī’s methodological and epistemological approach to resolving the problem of the relationship between reason and revelation. The folllowing section will exemine how Ibn Taymīyah responded to al-Rāzī, and the criticism he leveled against him. The final section will assess the debates, evaluating the extent to which Ibn Taymīyah succeeded in refuting al-Rāzī and identifying any misunderstandings he may have had regarding al-Rāzī’s arguments.